THE EFFECT OF PERFORMANCE AUDITS ON GOVERNMENT APPARATUS ON THE QUALITY OF PUBLIC SERVICES IN BANJARSARI SUB-SUB-DISTRICT SURAKARTA - Maya Widyana Dewi; Nisa Budianti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
This study examines the effect of performance audit of the government apparatus on the quality of public services in the Banjarsari sub-sub-district of Surakarta. This research method is descriptive with a qualitative approach. As for the location of the study in Banjarsari sub-district, the research population consisted of 92 people, consisting of the sub-district apparatus and the community in Banjarsari Sub-district. The purpose of this study was to find out (a) the effect of quality audit on work results, audit the quantity of work and audit timeliness on the quality of public services partially; (b) Effect of quality audit on work results, audit quantity of work results and audit timeliness of quality of public services simultaneously; (c) Which performance audit variable is the most influential on the quality of public services in Banjarsari Sub-district. The data obtained from interviews, collected and processed using the SPSS 23 For Windows Program. The results of the study are (a) quality audit of work results and audit of timeliness have a partial effect on the quality of public services, while auditing the quantity of work is not; (b) quality audit of work results, audit of quantity of work and audit of timeliness simultaneously affect the quality of public services; (c) The most influential performance audit variable is the audit of work quality.